Revitalisasi Konsep Publik Dalam Pemikiran dan Praktek Pembangunan Kota Bandung Lestari - Pius Suratman Kartasasmita (Centre for Public Policy and Management Studies, 2015)
Sustainable development is defined as the ability to ensure the fulfillment of the needs of the present without sacrificing the ability of future generations to meet their needs. The concept of sustainable urban development is crucial because at the beginning of the 21st century, more than half of the world's population live in urban areas. By using the concept of sustainable development and comparing the empirical facts about the reputation of the city of Bandung with other cities in Indonesia, this paper aims to a hypothesis stating that the realization of becoming a champion city of Bandung, as politically announced by its mayor, remains a tremendous challenge. Four critical issues need to be addressed, both by city government of Bandung as well as by its citizens, in order to promote sustainable urban development. These are, firstly, how to meet the considerable needs of the entire population of Bandung as the fight against poverty through employment and adequate public services. Secondly, how to establish a political system that guarantees the participation of the population Bandung effectively in the decision making process and ensure the application of greater democracy in both national and international levels. Thirdly, how to control the number of population and to promote lifestyle changes, both the manager and the people. Fourthly, how to build political will at encouraging all of them can be realized. At the end, this article concludes that the revitalization of publicness as central concept in sustainable development has now met its momentum, yet it needs the tireless efforts.